A community based cross sectional study of breastfeeding practices of nursing mothers at block Phagi, district Jaipur (Rajasthan) - Meharda, Bharat; Dixit, Mukul (International Journal Of Community Medicine And Public Health, 2017)
Background: Children are god gifted to society and we are responsible for every need of children. We can give them proper nourishments, care and good health. Breast milk is optimal food for the new born. Breastfeeding is one of the most important determinants of child survival, prevention of childhood infections. Methods:Community based cross sectional study was conducted at block Phagi, Jaipur, (Raj.), India on 300 mothers having children between 6 months to 24 months of age. Self-administered questionnaire was used to collect information on breastfeeding practices. Results: Out of 300 nursing mothers, majority of the participants 129 (43.00%) were the age group of 18-23 years followed by 118 (39.33%) from 24-29 years of age group. Majority of study participants 110 (36.66%) were illiterate. 156 (52.00%) participants were belonged to V SES. Large number of 188 (62.66%) of infants had pre-lacteal feeds. 202 (67.33%) of children had not Exclusive Breast Fed. Conclusions:This study relived that need to creating an awareness of the demerit of pre-lacteal feeds and advantages of colostrum, exclusive breastfeeding in rural area.